Cost and Cost-Effectiveness Assessments of Newborn Screening for Critical Congenital Heart Disease Using Pulse Oximetry: A Review - Scott D. Grosse; Cora Peterson; Rahi Abouk; Jill Glidewell; Matthew E. Oster (MDPI AG, 2017)
Screening newborns for critical congenital heart disease (CCHD) using pulse oximetry is recommended to allow for the prompt diagnosis and prevention of life-threatening crises. The present review summarizes and critiques six previously published estimates of the costs or cost-effectiveness of CCHD screening from the United Kingdom, United States, and China. Several elements that affect CCHD screening costs were assessed in varying numbers of studies, including screening staff time, instrumentation, and consumables, as well as costs of diagnosis and treatment. A previous US study that used conservative assumptions suggested that CCHD screening is likely to be considered cost-effective from the healthcare sector perspective. Newly available estimates of avoided infant CCHD deaths in several US states that implemented mandatory CCHD screening policies during 2011-2013 suggest a substantially larger reduction in deaths than was projected in the previous US cost-effectiveness analysis. Taking into account these new estimates, we estimate that cost per life-year gained could be as low as USD 12,000. However, that estimate does not take into account future costs of health care and education for surviving children with CCHD nor the costs incurred by health departments to support and monitor CCHD screening policies and programs.